2001
DOI: 10.1063/1.1332080
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical investigation of the thiophene/aluminum interface

Abstract: The adsorption of thiophene and 2, 2′-bithiophene on Al(111) has been studied using thermal desorption spectroscopy (TDS), angle-resolved UV photoemission (ARUPS), and work function measurements. Ab initio density functional theory calculations have been performed for thiophene on Al(111). Both thiophene and bithiophene bond only very weakly to Al(111), as indicated by TDS and calculations of the thiophene absorption energy, which is found to be only 0.54 eV. There is no indication of π-bonding in either the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…It was found that aluminum interacts strongly with thiophene in the latter case, but only weakly in the former one. This was in agreement with previously observed weak bonding of thiophene on Al(1 1 1) by Blyth et al [8] and studies of aluminum deposition on oligo-and polythiophenes [1].…”
Section: Introductionsupporting
confidence: 93%
“…It was found that aluminum interacts strongly with thiophene in the latter case, but only weakly in the former one. This was in agreement with previously observed weak bonding of thiophene on Al(1 1 1) by Blyth et al [8] and studies of aluminum deposition on oligo-and polythiophenes [1].…”
Section: Introductionsupporting
confidence: 93%
“…The metallic states associated with the brim sites, on the other hand, have the ability to donate and accept electrons and thus act as catalytic sites very much like ordinary catalytically active metal surfaces. Whereas many catalytically active metal surfaces (Fe, Ni, Mo to mention a few [50][51][52][53][54]) are poisoned by H 2 S and strongly bonded sulfur residues, the fully sulfurcoordinated brim sites of the MoS 2 nanoclusters are clearly not. Compared to the reactive metals on one hand and the inert basal plane of the MoS 2 nanoclusters on the other, the metallic brim sites seem to offer a more optimum bonding strength for the adsorption of thiophene.…”
Section: Discussionmentioning
confidence: 99%
“…The molecules interact with the metal in several ways (see Fig. 2), i.e., metal polarization (e.g., tris-(hydroxyquinoline)Al (Alq) on Ag, [15] or naphthalene on Cu [26] ), coupling of electronic states (e.g., C 6 F 5 S ± on Cu [14] ), partial charge exchange (ionic bond formation by thiophene on Al [27] ), or even formation of new chemical species by covalent bond formation, (organometallic complex formation of Alq on Mg [28] ). The importance of metal±molecule interactions is also clear from the inversion of dipole direction upon adsorption of benzoic acids on indium tin oxide (ITO) or on Al.…”
Section: Metal±molecule Contactsmentioning
confidence: 99%